PHOTOSYNTHETIC ACCLIMATIZATION IN ZYGOTIC EMBRYO CULTURED PLANTLETS OF COCONUT (COCOS NUCIFERA L.) - S. Naresh Kumar; V. Rajagopal; Anitha Karun (International Coconut Community, 2001)
It is important to understand the physiological acclimatization process in order to provide the favorable growing conditions, to increase the survival rate and to produce vigorous seedlings for field planting for better establishment. These aspects assume significance because the embryo culture technique is used for germplasm collection in coconut. The zygotic embryos from eight month old selfed nuts from West Coast Tall (WCT) cultivar of coconut were collected for embryo culture. The field planted seedlings produced by embryo culture and those raised from nursery were compared for photosynthetic activity under field grown conditions. Photosynthetic and water relation parameters were studied in the embryo cultured plantlets at different stages of acclimatization under green net house conditions. The photosynthetic rate increased gradually during acclimation with maximum rate atfour months after transfer to pots (under 50% shade; stage 4). The embryo cultured plantlets had higher photosynthetic rates compared to the nursery raised plants under field conditions. Transpiration rate increased with stage during acclimation. Embryo cultured plants had low transpiration rate as compared to the nursery raised plants. Consequently embrvo cultured plants had higher WUE (A/E). The WUE increased during acclimation. The Fv/Fm ratio increased gradually from 0.69 to 0.72 till stage 4. The field‑grown embryo culture plants had higher Fv/Fm compared to the nursery raised plant. This increase in Fv/Fm during acclimation indicated the increase in photochemical activity and photosystem II electron transport efficiency. The study indicated increase in photosystem efficiency and carbon assimilation efficiency of embryo cultured plantlets of coconut during acclimatization.